Synthesis of homogeneously dispersed manganese oxide/ carbon 3D nanocomposites and their electrochemical performance in lithium-ion batteries. Issue 12 (15th August 2018) - Qi, Jie; Zhu, Youyu; Ding, Ranran; Zhang, Jizong; Chang, Panpan; Jiao, Miaolun; Wang, Chengyang
Abstract: A MnOx/carbon nanocomposite was synthesized from a novel pitch-derived amphiphilic carbonaceous material (ACM). Characterization of this nanocomposite reveals that the nanosized manganese oxide particles are uniformly embedded in a porous carbon framework. When evaluated as the anode for lithium-ion batteries (LIBs), the structural features of the nanocomposite lead to an enhanced electrochemical performance with a high reversible capacity of 900 mAh g −1 at 50 mA g −1, excellent cyclic stability (620mAh g −1 at 300 mA g −1 after 500 cycles) and good rate performance ( 320mAh g −1 at 4 A g −1 ). The desirable electrochemical properties of the nanocomposite combined with its simple hybridization method make the prepared composite a promising electrode material for high-performance LIBs.